MRI in head and neck tumours - Rabindran Chandran; D Sharad Gedam (International Journal of Medical Research and Review, 2017)
Head and neck cancer are prevalent reason for cancer. Compared to CT, MRI has better tissue, spatial and contrast resolution, Non-ionizing radiation, Non-invasiveness, Multiplanar imaging and soft tissue definition.